Congenital Thoracic Venous Anomalies in Adults: Morphologic MR Imaging - Ruano, CA (2016)
Congenital anomalies of the thoracic veins are rare yet important developmental abnormalities, usually classified into systemic and pulmonary. They may be encountered incidentally; as such the radiologist must be aware of their imaging presentation and clinical relevance. Furthermore, to understand these anomalies, knowledge of the embryological development and of the normal anatomy of the thoracic veins is required. In the age of non-invasive imaging modalities, magnetic resonance is paramount for the characterization of these developmental abnormalities.